2011
DOI: 10.1016/j.bbmt.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Treatment for Epstein-Barr Virus DNAemia after Alternative-Donor Hematopoietic Stem Cell Transplantation

Abstract: We report 55 patients undergoing an alternative-donor hematopoietic stem cell transplantation (HSCT) who developed Epstein-Barr virus (EBV) DNAemia, with >1000 EBV copies/10(5) peripheral blood mononuclear cells (PBMCs), and were treated with rituximab (375 mg/m(2)). The median patient age was 47 years (range, 20-65 years), and graft sources were mismatched family members (n = 4), unrelated donors (n = 46), and unrelated cord blood (n = 5). The conditioning regimen included antithymocyte globulin (ATG) in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 25 publications
4
43
0
Order By: Relevance
“…[16][17][18] Furthermore, 'pre-emptive' treatment strategies in response to EBV DNAemia, with or without accompanying clinical evidence of EBV-associated disease, have been widely incorporated into clinical practice. 14,16,[18][19][20][21] However, this has been predominantly based on uncontrolled, single-centre studies encompassing heterogeneous methods of T-cell depletion and small numbers of PTLD events.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Furthermore, 'pre-emptive' treatment strategies in response to EBV DNAemia, with or without accompanying clinical evidence of EBV-associated disease, have been widely incorporated into clinical practice. 14,16,[18][19][20][21] However, this has been predominantly based on uncontrolled, single-centre studies encompassing heterogeneous methods of T-cell depletion and small numbers of PTLD events.…”
Section: Introductionmentioning
confidence: 99%
“…4 The real incidence and prognosis of EBV disease are difficult to evaluate due to differences in the PCR methods used to test EBV DNA, the quantitative PCR thresholds for therapeutic intervention and the diversity of criteria for defining high-risk patients. 5 Efforts to improve immune responses by reducing immunosuppressive drugs remain as one of the cornerstones of management but are not applicable to patients with active GVHD; 6,7 thus, eliminating B lymphocytes with the anti-CD20 monoclonal ab Rituximab is the most feasible treatment. 7 In the current study we compare the incidence and prognosis of EBV-related complications between patients with baseline highrisk characteristics for PTLD and patients affected by refractory GVHD, prospectively monitored for EBV DNAemia with early institution of Rituximab as pre-emptive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Use of rituximab to reduce CD20 þ cells forms a second pillar and appears most effective when employed early. 9 However, combination immune-chemotherapy may be required to treat monomorphic PTLD. 10,11 Novel approaches have been designed to enhance the T-cell reactivity, and include the use of DLI and EBV-specific cytotoxic T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of infection is important as it allows prompt reduction of immune-suppressive treatment and rituximab to be given pre-emptively, and this approach is increasingly being advocated in guidelines for managing high-risk SCT recipients. 9,13,14 A cut-off value for PCR of 1000 copies per mL is thought to be predictive of the development of EBV disease. 15,16 Several studies have shown that EBV monitoring and early treatment is feasible, and can prevent EBV disease.…”
Section: Introductionmentioning
confidence: 99%